CLIL and its potential application in primary English classes in an Islamic school - Rabbania Zaikalina; Muhammad Amin (Universitas Islam Sultan Agung, 2026)
This study explored the emergence of soft Content and Language Integrated Learning (CLIL) practices in English classrooms at an Islamic primary school in Indonesia. While CLIL is widely implemented in an international context, its application in local schools remains limited and often unintentional. This research aimed to examine how English teachers integrate the principles of content, language, and cultural values into their classroom practices, through a qualitative study involving classroom observations, interviews and document analysis. The findings reveal that teachers frequently integrated daily-life themes and Islamic cultural values into English instruction while employing communicative strategies to support language learning. However, cognitive engagement and cross-curricular integration remained limited due to limited instructional time and the absence of a formal CLIL approach. Despite these challenges, the findings suggest that soft CLIL principles can emerge naturally in Islamic primary school contexts. This study contributes to the growing literature on CLIL in Indonesian TEYL by providing empirical evidence of emerging soft CLIL practices and highlighting contextual considerations that may inform teacher professional development and future CLIL implementation in similar EFL primary education settings.